MO1051KNOWLEDGE, ATTITUDE AND ACCEPTANCE OF TELENEPHROLOGY SERVICES AMONG PATIENTS IN NEPHROLOGY: A STUDY FROM INDIA. (29th May 2021) - Subbiah, Arunkumar; George, Kristin; Agarwal, Sanjay Kumar
Abstract: Background and Aims: There is an increasing burden of kidney diseases in developing countries like India where access to specialist care is available only to a small proportion of patients. Telemedicine, has been relatively less used in India especially in public sector hospitals. The current study was designed to assess the patient's knowledge, attitude and acceptance of telenephrology services at our institute, a public sector hospital in a developing country. Method: This study is a cross-sectional survey carried out among patients who had availed our telenephrology services during the preceding three months. A total of 150 patients were selected by stratified random sampling from the list of attendees of telenephrology consultation in the past 3 months. The questionnaire was administered in local language by telephone interview method. The frequency distributions and average and median values for each of the questionnaire variables were calculated using SPSS software. Results: The average age of the study cohort was 42.52 ± 15.1 years (17 – 83yrs). 68% of the patients were males. The questionnaire was answered by the patient himself/herself in 56% cases, spouse in 14.0% and children in 20.7% cases. 51.3% patients were graduates or post graduates. 40.7% patients belonged to the upper middle and 39.3% belonged to the lower middle socioeconomic class. 54.6% patients were residing in towns, 28.7% in cities and 16.7% in villages. Prior to the telenephrology service, the median distance travelled to attend our OPD was 113.5 (3 – 2249 km). Attendees incurred loss of work in 54.7% cases. Information about availability of telenephrology services was obtained from institutional helpline number by 59 (39.3%) patients while 50 (33.3%) patients obtained it from the internet. Others got information from friends, television or short message service (SMS). The average number of teleconsultations was 2 per patient. A large majority of patients (99.3%) felt that Telenephrology service was a right approach during the COVID-19 pandemic. On asking how they felt regarding Telenephrology experience, 70.67% said they were very happy, 25.3% were happy and 4.0% said they were apprehensive or doubtful. 96.6% patients said that they were confident discussing their complaints over phone. 92.6% patients were comfortable sharing reports over phone while 7.3% needed help from caretakers. Regarding the problems faced during teleconsultation, 36% patients responded that they wish to see the doctor in person to feel satisfied while 3.3% found difficulty in understanding drug dosages. 86% patients felt that Telenephrology services should continue even after the COVID pandemic. Conclusion: In developing countries like India, with the majority of the population residing outside major cities, wherein the accessibility to a specialist is limited and the digital development outscores the physical infrastructure, Telenephrology has huge potential to provide quality nephrology care to the remotest parts of the country.